2015
DOI: 10.1104/pp.15.00839
|View full text |Cite
|
Sign up to set email alerts
|

Variability and constancy in cellular growth of Arabidopsis sepals

Abstract: Growth of tissues is highly reproducible; yet, growth of individual cells in a tissue is highly variable, and neighboring cells can grow at different rates. We analyzed the growth of epidermal cell lineages in the Arabidopsis (Arabidopsis thaliana) sepal to determine how the growth curves of individual cell lineages relate to one another in a developing tissue. To identify underlying growth trends, we developed a continuous displacement field to predict spatially averaged growth rates. We showed that this disp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
42
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 45 publications
0
42
0
1
Order By: Relevance
“…Here, we characterize the dynamic formation of cuticular ridges on the Arabidopsis floral organ epidermis in a developmental context. We use the sepal as a model system because it is the outermost floral organ, which is accessible for live imaging and cellular growth analysis (Roeder et al, 2010(Roeder et al, , 2012Qu et al, 2014;Tauriello et al, 2015;Hong et al, 2016). Our results show that cuticular ridge formation proceeds from the tip to the base of the sepal, coincident with the wave of cellular maturation typified by the cessation of cell division and transition to slow cell growth.…”
Section: Introductionmentioning
confidence: 94%
“…Here, we characterize the dynamic formation of cuticular ridges on the Arabidopsis floral organ epidermis in a developmental context. We use the sepal as a model system because it is the outermost floral organ, which is accessible for live imaging and cellular growth analysis (Roeder et al, 2010(Roeder et al, , 2012Qu et al, 2014;Tauriello et al, 2015;Hong et al, 2016). Our results show that cuticular ridge formation proceeds from the tip to the base of the sepal, coincident with the wave of cellular maturation typified by the cessation of cell division and transition to slow cell growth.…”
Section: Introductionmentioning
confidence: 94%
“…diploid plants have ploidy between 2C and 32C and vary ∼40fold in length (Roeder et al, 2010) ( Figure 1D). Live imaging of Arabidopsis sepal pavement cells has shown that endoreduplicating cells grow at the same relative rate, on average, as their dividing neighbors (Tauriello et al, 2015); in essence, endoreduplicated cells are larger because they grow without being halved by division (Roeder et al, 2010). Endopolyploidy has also been linked to cell fate: nascent trichomes in which endoreduplication is blocked often lose their identity (Bramsiepe et al, 2010), and pavement cells differ in gene expression based on their level of endopolyploidy (Roeder et al, 2012;Schwarz and Roeder, 2016).…”
Section: Two Kinds Of Ploidy Change Occur In Plantsmentioning
confidence: 99%
“…During the development of Arabidopsis thaliana ’s outmost floral organ, the sepal, equivalent epidermal cells in the primordium differentiate to produce a scattered pattern of giant cells that are interspersed between smaller cells (Figure 1A–F; Roeder et al, 2010, 2012; Tauriello et al, 2015). The sepal is a useful model system because the giant cell patterning process can be live imaged from the earliest stages of initiation through giant cell differentiation.…”
Section: Introductionmentioning
confidence: 99%